The Subtextual Significances of Pragmatic Equivalence in Translating Humor - Ni Nyoman Sarmi; Rommel Utungga Pasopati; Dyah Ayu Ratna Jelita; Yoshua Veron Handika Putra Siadari; Agischa Putri Agil; Muhammad Daffa Firzatullah (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This article examines the importance of pragmatic equivalence in translating humor, a crucial yet often challenging aspect due to humor’s deep reliance on cultural context, implicature, and audience interpretation. Pragmatic equivalence emphasizes the conveyance of implicit meaning through communication principles such as those proposed by Grice, where coherence takes precedence over mere lexical and grammatical cohesion. In humor translation, coherence refers to the interconnectedness of meaning based on shared context and knowledge between the author and the audience, rather than simply the structure of sentences. However, humor is inherently ambiguous and open to multiple interpretations, making its meaning not always directly transferable. A single mistranslated element can alter the entire comedic effect, as humor is often highly culture-specific. In this case, the translator’s role extends beyond language transfer to bridging the knowledge gap that the target audience might have, sometimes at the cost of the humor’s spontaneity. This challenge creates a dilemma between preserving natural comedic effect and delivering accurate meaning. As a result, humor translation often leans toward either overly literal or overly liberal approaches, each with the risk of losing essential nuance. Therefore, pragmatic equivalence involves more than just finding corresponding meanings; it also requires sensitivity to the social and cultural contexts that shape audience responses. The novelty of this study lies in its focus on the unique complexity of humor translation, making it a valuable contribution to the fields of literary studies, linguistics, and translation studies.